Peningkatan Pelayanan Pemungutan Pajak Bumi Dan Bangunan Oleh BPKPAD Kabupaten Sukoharjo - Amaliya Firdausa; Defani Rizky Rahmadzani; Denia Nur Fadillah; Sudiyanto Sudiyanto (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Land and Building Tax is a levy that must be paid for the existence of land and buildings that provide benefits and socio-economic status for a person or entity who has rights or receives benefits.Collection of Land and Building Tax is revenue from the taxation sector which is the right of the Regional Government as original regional income and is a source of funds to carry out regional development. Cooperation from all implementing officers and the community must be carried out to support an increase in Original Regional Income, especially Land and Building Tax. This type of research falls into qualitative analysis. Qualitative analysis aims to provide an in-depth explanation of a phenomenon by collecting comprehensive data. To understand and explain the land and building tax collection services at the Sukoharjo Regency Regional Revenue and Asset Financial Management Agency, there are several factors that need attention. The results of the research describing the Land and Building Tax collection services during the research show that land and building tax collection by BPKPAD has been carried out in accordance with the expectations of the local community, namely taxpayers. However, maximum results have not been achieved because there is still one problem. This means that there is no definite date for tax collection by the tax collector. It was also found that there were still obstacles in collecting land and building tax at the Financial Management Agency.